Hubungan Penggunaan Media Digital Terhadap Fear of Missing Out Pada Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana - Zakaria, Ady; Zuryani, Nazrina; Aditya, I Gusti Ngurah Agung Krisna (JURNAL ILMIAH SOSIOLOGI: SOROT, 2024)
The objective of this research is to investigate the existence of a significant association between the use of digital media, namely social media and e-Learning, and the phenomenon known as Fear of Missing Out (FOMO) among students from the Faculty of Social and Political Sciences (FISIP) at Udayana University. Przyblylski's (2013) theory of FOMO will be used to guide the quantitative research strategy. A sample size of 128 students was collected via distributing a Google Form link to complete the questionnaire, with a margin of error of 5% (0.05). The population for this research included all currently enrolled FISIP students who were taking lectures in their 7th semester, with a total of 321 individuals. The sampling approach used was the Slovin formula, which is represented by the equation n = N: 1 + Ne2. This study used observation and questionnaires as its data collection methods. This inquiry included classical assumption testing, multiple linear regression, correlation analysis, and pooled variance testing. The findings of this research indicate that there is no statistically significant relationship between the usage of e-Learning by FISIP Unud students and FOMO. As a result, the hypothesis Ha1 is rejected and the hypothesis H01 is accepted. A correlation value of 0.327 suggests a weak association between FOMO and e-Learning in the correlation relationship. The usage of social media has a strong correlation with the fear of missing out (FOMO) among FISIP Unud students. This is supported by the statistical significance of the social media variable (X2) on FOMO (Y), with a p-value of 0.000 < 0.05, and a t-value of 5.172, which is more than the critical t-value of 1.657. Thus, Ha2 is deemed acceptable whereas H02 is deemed unacceptable. The correlation data indicate a moderate link (r=0.499) between the fear of missing out (FOMO) and social media.